Glass marking by laser transfer implantation (LTI) of plasmonic nanoparticles. (November 2022) - Ihlemann, J.; Richter, L.J.; Meinertz, J.; Wunderlich, J.; Schindler, N.; Günther, A.; Oberleiter, B.; Rainer, T.
Highlights: Gold nanoparticles embedded in glass are formed by laser transfer implantation (LTI). LTI combines laser induced forward transfer (LIFT) and laser implantation in one single process. LTI enables glass marking with colored labels. Abstract: Gold nanoparticles in the near surface volume of glass are generated by combining laser-induced forward transfer (LIFT) and laser implantation into one single laser process called laser transfer implantation (LTI). Nanosecond pulses of a KrF excimer laser at 248 nm wavelength are used to transfer and implant the material from a gold- coated, UV-transparent polymer film into soda lime, borofloat, and flint glasses. The process can be applied for marking glass with colored labels consisting of spectrally selectively absorbing plasmonic nanoparticles.